2015
DOI: 10.1042/cs20140732
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis is a key pathogenic event in human and experimental murine models of non-alcoholic steatohepatitis

Abstract: Hepatocyte cell death, inflammation and oxidative stress constitute key pathogenic mechanisms underlying non-alcoholic fatty liver disease (NAFLD). We aimed to investigate the role of necroptosis in human and experimental NAFLD and its association with tumour necrosis factor α (TNF-α) and oxidative stress. Serum markers of necrosis, liver receptor-interacting protein 3 (RIP3) and phosphorylated mixed lineage kinase domain-like (MLKL) were evaluated in control individuals and patients with NAFLD. C57BL/6 wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
228
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(240 citation statements)
references
References 48 publications
8
228
1
3
Order By: Relevance
“…Th17 cells gen, whereas the downregulated cluster was enriched for genes involved in lipid metabolism ( Figure 2E). Consistently, mRNA expression of genes involved in liver fibrosis, including Col1a1, Acta2, Tgfb1, and Mmp13, and hepatic inflammation, including Previous studies have demonstrated that treatments of primary hepatocytes with a combination of palmitic acid (PA) and TNF-α (PA/TNF-α) robustly triggered cell death that mimics NASHinduced liver injury (21,37). To investigate whether Nrg4 plays a direct role in the regulation of hepatocyte death, we treated primary hepatocytes transduced with GFP or ErbB4 adenovirus with PA/TNF-α.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Th17 cells gen, whereas the downregulated cluster was enriched for genes involved in lipid metabolism ( Figure 2E). Consistently, mRNA expression of genes involved in liver fibrosis, including Col1a1, Acta2, Tgfb1, and Mmp13, and hepatic inflammation, including Previous studies have demonstrated that treatments of primary hepatocytes with a combination of palmitic acid (PA) and TNF-α (PA/TNF-α) robustly triggered cell death that mimics NASHinduced liver injury (21,37). To investigate whether Nrg4 plays a direct role in the regulation of hepatocyte death, we treated primary hepatocytes transduced with GFP or ErbB4 adenovirus with PA/TNF-α.…”
Section: Resultsmentioning
confidence: 87%
“…Necroptosis releases intracellular danger-associated molecular patterns, such as high-mobility group B1 (HMGB1), that have potential to trigger robust inflammatory response (13,19). RIPK3 deficiency attenuates liver injury, steatosis, inflammation, and fibrosis in an MCD diet-induced NASH mouse model, implicating necroptosis in the liver as a contributor to NASH (20,21). As such, targeting hepatocyte cell death may provide an effective approach to alleviating or reversing NASH progression (22).…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, SPECT/μCT imaging using both Tc-99m-labelled Nbs clearly showed an increase in the signal in mice fed a MCD diet. Since this disease associated with massive shrinkage of the liver, the increase in both the KC numbers/g of liver and the SPECT/μCT signal could be largely due to a documented clustering of CD11b + immune cells [25] combined with hepatocyte necroptosis [32]. Supplementing the mice for 1 week with standard chow reverted the MCD phenotype such that there were no longer differences in any of the above mentioned investigated parameters, suggesting that these mice are tending towards recovery from disease.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, the Ripk3 −/− genotype, the intraperitoneal delivery of Ripk3 -targeting antisense oligonucleotides, or the administration of dabrafenib (an FDA-approved inhibitor of oncogenic BRAF that also suppresses RIPK3 kinase activity) provides considerable hepatoprotection in mouse models of acetaminophen toxicity (134, 170, 171), concanavalin A–driven hepatitis (134), ethanol and dietary intoxication (172, 173), and nonalcoholic steatohepatitis (NASH) (174, 175). Along similar lines, mice treated with Nec-1 exhibit an increased resistance to the hepatotoxic effects of acetaminophen as compared with control animals (134).…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%